Pemanfaatan Remitensi Buruh Migran Perempuan untuk Meningkatkan Kesejahteraan Keluarga yang Ditinggalkan - Siti Imroatul Khuriah; Agus Purnomo (Geography Education Study Program, Universitas Kanjuruhan Malang, 2023)
The purpose of this study was to determine the effectiveness of the use of augmented reality learning media on geography subjects in class X SMAN 36 Jakarta. This research uses an experimental method with Nonrandomized Control Group Pretest Posttest Design. The population of this study were students of class X SMAN 36 Jakarta with research samples selected by randomized sampling technique, namely X E1 as the experimental class and X E2 as the control class. Data collection techniques used were tests on two classes and distributing questionnaires filled out by experimental class students. Some of the data analysis techniques used are instrument tests, data tests as analysis requirements and data analysis tests. Based on the test results, the instrument was declared valid and reliable and the data was declared normal and homogeneous. The results showed that augmented reality learning media was declared effective to improve students' learning outcomes in geography class X SMAN 36 Jakarta with a significance value of 0.000 <0.05 and an N-Gain value of 71.069%, which included the effective category. So educators can utilize the media to be used as a praga tool that facilitates the learning process because it is proven to be able to provide an increase in student learning outcomes. For future research, it is hoped that this augmented reality media can be used in other learning materials.